Analysis of the Impact of Gadget Use on the Learning Behavior of Fifth-Grade Students at SD Negeri 20 Palu - Langgari, Tasya; Azizah, Azizah; Nuraini, Nuraini; Nasrullah, Nasrullah; Rini, Eva Setya (FKIP - Universitas Riau, 2026)
Gadgets are electronic devices such as tablets, smartphones, and laptops equipped with advanced technology to meet educational needs. These devices are used in educational institutions for accessing course materials, searching for information, and using educational applications. This study aims to analyze the impact of gadget use on the learning behavior of fifth-grade students at SD Negeri 20 Palu and examine the role of teachers and parents in guiding their use to support learning. The study employed a qualitative descriptive approach with field study methods. Research subjects consisted of fifth-grade students, homeroom teachers, and parent representatives. Data collection techniques included observation, interviews, questionnaires, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that gadget use can have positive or negative impacts on student learning behavior. When used for educational purposes, gadgets increase learning motivation, but uncontrolled use decreases concentration, learning discipline at home, and academic achievement. Teachers are responsible for regulating, supervising, and directing gadget use at school, while parents supervise, limit time, and provide sanctions and rewards at home. Collaboration between teachers and parents is essential for effective gadget management.